2016
DOI: 10.1038/srep28355
|View full text |Cite
|
Sign up to set email alerts
|

CTCF contributes in a critical way to spermatogenesis and male fertility

Abstract: The CCCTC-binding factor (CTCF) is an architectural protein that governs chromatin organization and gene expression in somatic cells. Here, we show that CTCF regulates chromatin compaction necessary for packaging of the paternal genome into mature sperm. Inactivation of Ctcf in male germ cells in mice (Ctcf-cKO mice) resulted in impaired spermiogenesis and infertility. Residual spermatozoa in Ctcf-cKO mice displayed abnormal head morphology, aberrant chromatin compaction, impaired protamine 1 incorporation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 73 publications
(118 reference statements)
5
54
0
14
Order By: Relevance
“…In bull spermatozoa, a study by Hur et al [68] reported that the protein of KCK4 localizes to the equatorial region of acrosome reacted sperm, and that inhibitor of the K 2P channels reduces not only fertilization but also development of bovine and mouse embryos in vitro. Interestingly, a DMR was located in the CTCF gene, which has been associated with spermatogenesis and male fertility [70, 71]. The CTCF gene plays a critical role in genome-wide gene regulation and has roles in epigenetic reprogramming, gametogenesis and embryo development and is also associated with fertility, as reviewed by Franco et al [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bull spermatozoa, a study by Hur et al [68] reported that the protein of KCK4 localizes to the equatorial region of acrosome reacted sperm, and that inhibitor of the K 2P channels reduces not only fertilization but also development of bovine and mouse embryos in vitro. Interestingly, a DMR was located in the CTCF gene, which has been associated with spermatogenesis and male fertility [70, 71]. The CTCF gene plays a critical role in genome-wide gene regulation and has roles in epigenetic reprogramming, gametogenesis and embryo development and is also associated with fertility, as reviewed by Franco et al [70].…”
Section: Discussionmentioning
confidence: 99%
“…The CTCF gene plays a critical role in genome-wide gene regulation and has roles in epigenetic reprogramming, gametogenesis and embryo development and is also associated with fertility, as reviewed by Franco et al [70]. Indeed, a study by Hernandez-Hernandez et al [71] reported that mice with a conditional knock-out of the CTCF gene had smaller testis and spermatogenesis was impacted as several males were infertile. Moreover, spermatozoa of the CTCF-conditional knock-out mice also demonstrated aberrant histone retention and disrupted chromatin compaction.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomethylation of paternal allele is associated with inactivation of IGF2 and is the most relevant cause of Silver–Russell imprinting disorder (De Crescenzo et al., ). Moreover, CTCF mutations in male germ cells in mice are associated with impaired spermiogenesis and infertility (Hernandez‐Hernandez, Lilienthal, Fukuda, Galjar, & Hoog, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CTCF at sequence motifs in accessible sperm DNA was confirmed via ChIP-seq experiments (16). CTCF has been found to be essential for normal spermiogenesis, sperm fertility, and histone retention in mature sperm (39). Genome-wide Hi-C mapping experiments have uncovered the presence of compartments, CTCF-mediated loops, and topologically associating domains in sperm chromatin similar to those found in somatic cell lines and embryonic stem cells (16,37).…”
Section: D Organization Of Sperm Chromatinmentioning
confidence: 72%